Commit c148ac4d by Robbert Krebbers

### Prove `E2 ⊆ E1 → P ={E1,E2}=∗ P`.

parent b33a29de
 ... @@ -203,6 +203,13 @@ Section fupd_derived. ... @@ -203,6 +203,13 @@ Section fupd_derived. Lemma fupd_wand_r E1 E2 P Q : (|={E1,E2}=> P) ∗ (P -∗ Q) ={E1,E2}=∗ Q. Lemma fupd_wand_r E1 E2 P Q : (|={E1,E2}=> P) ∗ (P -∗ Q) ={E1,E2}=∗ Q. Proof. by rewrite fupd_frame_r wand_elim_r. Qed. Proof. by rewrite fupd_frame_r wand_elim_r. Qed. Lemma fupd_mask_weaken E1 E2 P `{!Absorbing P} : E2 ⊆ E1 → P ={E1,E2}=∗ P. Proof. intros ?. rewrite -{1}(right_id emp%I bi_sep P%I). rewrite (fupd_intro_mask E1 E2 emp%I) //. by rewrite fupd_frame_l sep_elim_l. Qed. Lemma fupd_trans_frame E1 E2 E3 P Q : Lemma fupd_trans_frame E1 E2 E3 P Q : ((Q ={E2,E3}=∗ emp) ∗ |={E1,E2}=> (Q ∗ P)) ={E1,E3}=∗ P. ((Q ={E2,E3}=∗ emp) ∗ |={E1,E2}=> (Q ∗ P)) ={E1,E3}=∗ P. Proof. Proof. ... ...
Markdown is supported
0% or
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment